2015
DOI: 10.1093/gbe/evv230
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive DNA and Plant Domestication: Variation in Copy Number and Proximity to Genes of LTR-Retrotransposons among Wild and Cultivated Sunflower (Helianthus annuus) Genotypes

Abstract: The sunflower (Helianthus annuus) genome contains a very large proportion of transposable elements, especially long terminal repeat retrotransposons. However, knowledge on the retrotransposon-related variability within this species is still limited. We used next-generation sequencing (NGS) technologies to perform a quantitative and qualitative survey of intraspecific variation of the retrotransposon fraction of the genome across 15 genotypes—7 wild accessions and 8 cultivars—of H. annuus. By mapping the Illumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 78 publications
(107 reference statements)
1
57
0
Order By: Relevance
“…The selected Divaricati species included three diploid (H. divaricatus, H. giganteus, and H. smithii), three tetraploid (H. hirsutus, H. californicus, and H. laevigatus), and one hexaploid species (H. tuberosus). Regarding H. annuus, previous studies reported high variability in the repetitive component between wild and cultivated genotypes (Mascagni et al, 2015). In this study, a wild accession from Illinois was chosen to represent H. annuus; this particular accession exhibits average features among wild H. annuus genotypes (Mascagni et al, 2015).…”
Section: Plant Materials and Dna Sequencingmentioning
confidence: 99%
See 3 more Smart Citations
“…The selected Divaricati species included three diploid (H. divaricatus, H. giganteus, and H. smithii), three tetraploid (H. hirsutus, H. californicus, and H. laevigatus), and one hexaploid species (H. tuberosus). Regarding H. annuus, previous studies reported high variability in the repetitive component between wild and cultivated genotypes (Mascagni et al, 2015). In this study, a wild accession from Illinois was chosen to represent H. annuus; this particular accession exhibits average features among wild H. annuus genotypes (Mascagni et al, 2015).…”
Section: Plant Materials and Dna Sequencingmentioning
confidence: 99%
“…Regarding H. annuus, previous studies reported high variability in the repetitive component between wild and cultivated genotypes (Mascagni et al, 2015). In this study, a wild accession from Illinois was chosen to represent H. annuus; this particular accession exhibits average features among wild H. annuus genotypes (Mascagni et al, 2015).…”
Section: Plant Materials and Dna Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis of 'genetic shock' suggests that interspecific hybridization may be accompanied by the proliferation or elimination of TEs leading to dramatic changes in a hybrid genome [32]. The dynamics of TEs, in particular, LTR retrotransposons, is supposed to be the main cause of plant genome size alterations on the evolutionary time scale [12,[33][34][35][36][37]. Recent findings have shown that TEs are population-specific and apparently involved in population divergence and speciation at the diploid level [38][39][40].…”
Section: Introductionmentioning
confidence: 99%